To the question of raising the level of citizens’ trust law enforcement officials (Journal of actual problems of jurisprudence, 2018)
This article considers the issues of improving the methods of obtaining information about criminal offences. Were studied the provisions of the State program of further modernization of law enforcement system for 2014-2020. In particular, studied the possibility of increasing law enforcement agencies provide public services in electronic form. The content of the public service law enforcement agencies information on criminal offences. The attention is focused on existing ways of obtaining information on criminal offences and their improvement in order to increase the level of trust of citizens to law-enforcement system.Key words: modernization, service, information, criminal offence, shelter, communication, application, acceptance, registration, ticket-notification.